2002
DOI: 10.1074/jbc.m110929200
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β Binds Trimers as Well as Monomers of the 75-kDa Neurotrophin Receptor and Activates Receptor Signaling

Abstract: p75NTR , a nerve growth factor co-receptor that has been implicated in apoptosis of neurons, is structurally related to Fas and the receptors for tumor necrosis factor-␣ that display ligand independent assembly into trimers. Using embryonic day 17 fetal rat cortical neurons and p75 NTR -expressing NIH-3T3 cells, we now show that p75 NTR exists as a trimer as well as a monomer. Furthermore, we have reported and others have confirmed that amyloid ␤ binds p75 NTR , and that this binding leads to apoptotic cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
133
2
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 38 publications
12
133
2
1
Order By: Relevance
“…55 One of the typical feature found in post-mortem studies on brains from AD patients is an overexpression of c-Jun, 56 which is also a hallmark of Ab-induced apoptosis in neuronal cultures. 17,44 This transcription factor was found to play a major role in Ab-induced neurotoxicity. 17,18 In the present study, we showed that the protective action of 12-LOX antisense oligonucleotide against Ab-mediated toxicity was associated with the suppression of c-Jun overexpression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 One of the typical feature found in post-mortem studies on brains from AD patients is an overexpression of c-Jun, 56 which is also a hallmark of Ab-induced apoptosis in neuronal cultures. 17,44 This transcription factor was found to play a major role in Ab-induced neurotoxicity. 17,18 In the present study, we showed that the protective action of 12-LOX antisense oligonucleotide against Ab-mediated toxicity was associated with the suppression of c-Jun overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Moreover, both c-Jun expression and activation were found to be increased following exposure of neurons to Ab, and recent data suggested a 12-Lipoxygenase and amyloid peptide toxicity A Lebeau et al critical role of this transcription factor in Ab-induced apoptosis. [17][18][19]43,44 We therefore investigated whether 12-LOX blockade could interfere with such an Ab-induced c-Jundependent apoptotic pathway in cortical cells.…”
Section: Blockade Of 12-lox Expression Disrupts a C-jun-dependent Ab-mentioning
confidence: 99%
“…An Abeta pathway, inducing TrkA phosphorylation directly by itself and indirectly by promoting NGF secretion (28), has recently been reported. p75 expression is also linked to changes occurring in AD (17,29), probably through its direct binding to Abeta 1-42 peptides (29,30). In addition, p75 mediates APP promoter activity, leading to an increase of secreted APP (31,32), and undergoes intramembrane ␣ and ␥ secretase-mediated processing to generate p75 CTF and p75 ICD fragments, respectively (11).…”
Section: Discussionmentioning
confidence: 99%
“…Localization of ADD, which has been more or less precisely determined depending on receptor, is indicated by double arrows. other cell-death-inducing ligands have been proposed for p75 NTR , such as pro-NGF (Lee et al, 2001b), b-amyloid (Yaar et al, 2002) and prion (Della-Bianca et al, 2001) peptides. The decision between ligandinduced apoptosis and ligand-inhibited apoptosis mediated by p75 NTR likely depends on cell type and development stage (Barrett and Bartlett, 1994).…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%